Aspects of the resorcinol-formaldehyde condensation - Waldron, Ronald Augustus Frank (Rhodes University, Faculty of Science, Department of Chemistry, 1954)
An attempt was made to producea -Î² or Ïª - resorcinyl alcohol from disubstituted resorcinyls. To accomplish this 3,5-dibromo-Î²-resorcylic acid was reacted with lithium aluminium hybride, a mild reducing agent, in an attempt to reduce the acid group to the alcohol group. This disubstituted resorcinol was recovered unchanged. 3,5-dibromo-Î²-resorcyl-aldehyde was reduced by lithium aluminium hydride, but, instead of the alcohol forming, resinification took place. 2-methyl- 4-ethylresorcinol and 4,6-diethyrecorinol were reacted with formaldehyde under alkaline and acidic conditions. In each case a resin formed. The above experlments indicated that condensation took place in the meta position of the resorcinol molecule. Trimethylresorcinol was therefore reacted with formaldehyde under alkaline conditions, resulting in a small quantity ot the alcohol derivative. A better yield of the alcohol derivative was obtained by the hydrolysis or the chloromathyl derivative. In pursuing this line, a seres of new compounds and their derivatives were prepared. The condensation of the alcohol derivative with trimethylresorcinol and also with resorcinol was investigated.
Keywords: Resorcinol; Formaldehyde